Program Kalurahan Online (Kaline) Sebagai Upaya Pengembangan BUMDes Kalurahan Margokaton Berbasis Digital - Sakir Sakir; Reni Budi Setianingrum; Bhakti Gusti Walinegoro; Afisa Afisa (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The main purpose of implementing the Kalurahan Online service program is to manage village profile data digitally, procurement and updating of websites and social media, and mapping of problems, as well as village potential to improve BUMDes performance. The method used is to provide assistance involving students and lecturers of the University of Muhammadiyah Yogyakarta to directly go to the field and develop/compile village profiles, website creation and training to improve reliable human resources. The first results obtained from this activity are that the Margokaton Village already has an online-based Profile Book and profile video that contains complete and up-to-date data so that it can be used as a reference for making village government policies. Then there is the latest design on the Instagram feed display of the Village-Owned Enterprises (BUMDes) and the Margokaton Kalurahan website to support the promotion of potential, especially local handicraft products. Developments that need to be carried out after this program include updating the up-to-date village profile and using active social media.